Subband mutiresolution by multi-object phase-only joint transform correlator - Bal, A (ELSEVIER GMBH, 2006)
Subband multiresolution technique presents decomposition and reconstruction properties for 2D images Using multichannel spatial filtering. Each subband image represents multiresolution of the input image. In this paper, optic subband multiresolution architecture is proposed based on multi-object phase-only joint transform correlator (JTC). Multichannel filtering is realized using multi-object input joint image that includes bipolar data. The bipolar data (containing positive, zero and negative values) is encoded by phase in the input and Fourier planes of the phase-only JTC. For image decomposition and reconstruction, two optoclectronic subband multiresolution architectures have been developed. Each architecture has been tested using a simulation program. (c) 2005 Elsevier GmbH. All rights reserved.
Keywords: subband multiresolution; joint transform correlation; phase encoding; image feature extraction; IMPLEMENTATION; Optics